Endocrine abnormalities and myopathy in Bloom's syndrome. Issue 6 (December 1977) - Ahmad, U; Fisher, E R; Danowski, T S; Nolan, S; Stephan, T
Abstract : Abnormal endocrine indices and myopathy have been variably present in two brothers with Bloom's syndrome (congenital teleangiectatic erythema, hypersensitivity to light, and growth retardation). These consisted of: (1) growth retardation with height and weight below the third centiles; in the younger one at age 14, hypoglycaemia failed to elicit a rise in growth hormone but did so in the older one at age 17; (2) serum TSH was raised in the older one in whom serum FSH and LH were also above the normal range; and (3) myopathy characterised by pronounced dilatation of the sarcoplasmic reticulum was present in the younger one; distinct reduction of muscle strength was shown in his older brother with ultrastructural alteration of skeletal muscle of unknown significance.